Interferência das construções sucessivas de Pequenas Centrais Hidroelétricas (PCH), sobre a ictiofauna do rio Sapucaí-Mirim-SP, Brasil - Souza, Diogo Freitas [UNESP] (2014)
The aim of this study was to characterize the composition and structure of the ichthyofauna of the Sapucaí - Mirim River (SP) in stretches under direct interference of Small Hydropower Plants (SHP’s), which are disposed in a cascade system along the river main axis. From upstream to downstream the sequence of SHP’s are: Palmeiras, Anhanguera and Retiro (under construction during the investigation). New plants are to be constructed, in the superior and inferior river stretches. Eight sampling campaigns, considering eight sampling points, were conducted quarterly from June/2011 until March/2013. As capture apparatus, gillnets were used with meshes ranging from 3 to 18cm between opposite knots, all with 20m length and height ranging 1.5 to 2.0 m, totaling 450 m² per sampling site. Sixty-six taxa of fishes were identified and distributed in six orders, 19 families and 41 genus. The most specious order was Characiformes (29 species), followed by Siluriformes (25), Perciformes (six), Gymnotiformes (four), Synbranchiformes and Cyprinodontiformes orders (one taxon each). The Sapucaí-Mirim is a highly specious river, considering its limited drainage area. The ichthyofauna composition in the areas under reservoirs influence follows the same pattern observed in large dams, with proliferation of small size species with high reproductive potential and reduced longevity. It is also noticeable for Sapucaí River the expressive richness and abundance of catfishes. These fish group is highly dependent on typical fluvial habitats threatened by dam construction, such as the riffles. The fish spatial distribution did not follow the pattern observed in large impoundments, probably due the reduced effect of reservoir compartmentalization in case of SHPs. Our results did not evidence the direct interference of SHPs construction on the ichthyofauna. Therefore, it is of fundamental importance to increase the monitoring area along the river, not only ...